STRATEGI KOMUNIKASI PENINGKATAN ENGAGEMENT (LIKE, SHARE, DAN COMMENT) TIKTOK @UNIVERSITAS DIPONEGORO DAN INSTAGRAM @UNDIP.OFFICIAL MELALUI PRODUKSI KONTEN VIDEO SEBAGAI PRODUCTION MANAGER DAN MEDIA PLANNER - Archelino Ivandra; Nurul Hasfi (Interaksi Online, 2026)
The development of social media has encouraged changes in digital communicationpatterns, particularly in the dissemination of information by educational institutions.Diponegoro University utilizes social media through the @undip.official account as a mediumfor public communication, information dissemination, and institutional image building.However, content management still needs to be optimized to enhance audience engagement.This professional project aims to implement a digital communication strategy through theproduction of video content on TikTok and Instagram platforms (@undip.official) in order toincrease engagement. The implementation was carried out through three stages: preproduction,production,andpost-productionofvideocontent,usingacommunicationstrategyapproachbasedontheAISASmodel(Attention,Interest,Search,Action,andShare).Inthisproject,theauthorwasresponsibleforpre-productionmanagement,productionmanagement,post-productionmanagement,targetaudienceanalysis,thedevelopmentandorganizationofacontentmatrix and media recommendations, content performance evaluation as well ascoordinating the content publication process. The results indicate an increase in the number ofproduced contents from 45 to 75 pieces of content, along with a rise in audience interactionssuch as likes, comments, and shares. Therefore, optimizing digital communication strategiesthrough creative content can improve the effectiveness of social media as a medium forinstitutional communication.